Conservative management of urachal anomalies - Dethlefs, Christopher R.; Abdessalam, Shahab F.; Raynor, Stephen C.; Perry, Deborah A.; Allbery, Sandra M.; Lyden, Elizabeth R.; Azarow, Kenneth S.; Cusick, Robert A. (Journal of pediatric surgery, 2019)
The purpose of this study was to evaluate trends in management of urachal anomalies at our institution and the safety of nonoperative care. Based on our experience managing urachal remnants from 2000 to 2010 (reported in 2012), we adopted a more conservative approach, including preoperative antibiotic use, refraining from using voiding cystourethrograms (VCUG), postponing surgery until at least six months of age, and considering nonoperative management. A retrospective analysis of urachal anomaly cases was conducted (2011–2016) to assess trends in practice. Charts indicating anomalies of the urachus were pulled and trends in management (nonoperative versus surgical treatment), VCUG and antibiotic use, and outcomes were reviewed. Data from 2000–2010 and 2013–2016 were compared. Our findings indicate care has shifted towards nonoperative management. A smaller proportion of patients from 2013–2016 was treated surgically compared to 2000–2010. Patients receiving nonoperative treatment exhibited lower rates of complication relative to surgically managed cases. VCUGs were eliminated as a diagnostic tool for evaluating urachal anomalies. Prophylactic preoperative antibiotic use was standardized. No patients with a known urachal remnant presented later with an abscess or sepsis. We find that a shift towards nonoperative treatment of urachal anomalies did not adversely affect overall outcomes. We recommend observing minimally symptomatic patients, especially those under six months old. Performance improvement. Level IV.